Scientific advances and evidence-based management in erectile dysfunction - Brock, Gerald; Chung, Eric (Translational Andrology and Urology, 2017)
Significant advances have been made in the diagnosis and treatment of erectile dysfunction (ED) over the last half century. In the early 1970’s, ED or previously known as impotence, was thought to be related to psychogenic causes as popularised by Masters and Johnson; however, advances in our understanding of molecular biological factors and mechanisms governing sexual function have demonstrated that the underlying pathogenesis for ED is frequently multifactorial in nature.